Bovine herpesvirus type 5 replication and induction of apoptosis in vitro and in the trigeminal ganglion of experimentally-infected cattle. (April 2018) - Rensetti, Daniel E.; Marin, Maia S.; Morán, Pedro E.; Odeón, Anselmo C.; Verna, Andrea E.; Pérez, Sandra E.
Highlights: Bovine herpesvirus (BoHV)-5 induced lower levels of apoptosis than BoHV-1. BoHV- induced apoptosis is cell type-specific. BoHV-induced apoptosis depends on the level of virus replication. Neuropathology by BoHV is associated with apoptosis and the innate immune response. Abstract: Bovine herpesvirus (BoHV) types 1 and 5 are neuroinvasive. Cases of BoHV-1-induced encephalitis are not as frequent as those caused by BoHV-5. In this study, the capability of BoHV-5 to induce apoptosis in cell cultures and in the trigeminal ganglion during acute infection of experimentally-infected cattle was analyzed. Apoptotic changes in cell cultures agree with the ability of the viral strains to replicate in each cell line. Marked differences were observed between the in vitro induction of apoptosis by BoHV-1Cooper and BoHV-5 97/613 strains. Apoptotic neurons were clearly evident in the trigeminal ganglion of BoHV-1-infected calves. For BoHV-5 a fewer number of positive neurons was observed. There is an association between the magnitude of bovine herpesviruses replication and the induction of apoptosis in trigeminal ganglion. These findings suggest that the induction of apoptosis and the innate immune response orchestrate the final outcome of alpha herpesviruses infection of the bovine nervous system.